Extraction and biological evaluation of Mycobacterium bovis extracellular vesicles as adjuvant and candidates for bovine tuberculosis vaccine - Sharifi Yazdi, Mohammad Kazem; Siadat, Seyed Davar; Monadi Sepidan, Alireza; Taheri Mirghaed, Ali; Khalieh-gholi, Mohammad; Sharifi Yazdi, Sarah; Saleh Safari, Mohammad; Sharifi Yazdi, Sina (The European Research Journal, 2022)
Objectives: BCG vaccine is the only virtual vaccine that has significantly helped control tuberculosis for 80 years. Bacteria naturally release extracellular vesicles (EVs) in different environments during the growth process. The use of extracellular vesicles is an alternative way to transfer ligands that are detected by host cells. Vesicles range in size from 50 nm to 250 nm in diameter and contain phospholipids, proteins, and lipopolysaccharides, and can carry additional factors such as toxins, adhesive, or immune system compounds that are important in pathogens. Therefore, this study aimed to evaluate these compounds as adjuvants or candidates for the bovine tuberculosis vaccine. Methods: In the present study, Mycobacterium bovis standard CRBIP7.121 was used. Extraction of membrane vesicles after mass culture was performed by a method based on ultracentrifugation and deoxycholate. After preparation and staining, the vesicles were examined by electron microscopy. Sample analysis was also performed by SDS-PAGE. The presence of LPS in the sample was measured by the LAL test. In addition, the harmlessness of bacterial EVs and the absence of any toxic agents in the sample were confirmed by pyrogenic tests in rabbits. Results: The protein content of membrane vesicles is equal to 1.25 and 1.32 mg/ml. In SDS-page evaluation, bands of 35, 40, 50, and 70 kDa were observed and then membrane vesicles were observed and confirmed by electron microscopy. The amount of vesicle toxin contained by the LAL test was reported in the permissible range. Conclusions: Discussion of the data obtained from the above research shows that at different stages of the purification process, EVs fully retained their spatial and natural form and lacked impurities. Therefore, due to the importance of external vesicles in developing immune responses, EVs extracted from M. bovis CRBIP7.121 can be considered a useful and effective immunogen against Mycobacterium infections.